Визначення та особливості технології блокчейн у сучасному світі - Поліщук, В. Г. (ХНУРЕ, 2023)
This work is focused on the blockchain technology, which provides secure data storage and transmission in a decentralized network based on a sequence of connected blocks. The security and reliability of data in the blockchain are ensured by cryptographic functions that guarantee the integrity and immutability of previously recorded information. The text also discusses the decentralized nature of the blockchain and the consensus principle, which allows for data management without a central authority and involves all network participants in the verification and confirmation of new data. The role of cryptographic algorithms in securing data and the importance of network nodes for maintaining a continuously available ecosystem are also highlighted